Survival Politics: Regime Security and Alliance Design on the Korean Peninsula. Issue 2 (28th March 2022) - Kim, Inwook; Woods, Jackson
Abstract: What determines states' willingness to institutionalize alliances? Contrary to conventional emphasis on system-level conditions, we argue that states pay close attention to the domestic political consequences of institutionalizing alliances. This is particularly true for unequal allies. Client regimes are disproportionately sensitive to alliance design, as it affects patron allies' ability to influence their military, distribute finance and arms, and legitimate preferred political groups. Two factors—power consolidation and political compatibility—determine whether the client views alliance institutionalization as complementary or conflictual with regime survival. The divergent alliance designs North and South Korea chose after the Korean War support our argument. An unresolved power consolidation process forced Kim Il-Sung to refuse formalizing the wartime alliance with the PRC, and Kim concluded a minimal treaty in 1961 after consolidating his power. In contrast, rapid consolidation left Rhee Syngman little to fear from continuing the highly institutionalized wartime alliance arrangement with the United States, which accepted his authority in the south. Our findings have important implications for alliance design, intra-alliance politics, and civil–military relations. Diseño de alianzas y seguridad del régimen de la política de supervivencia en la península de Corea